Analisis Validitas E-LKPD Interdisipliner Berbasis Projek Penguatan Profil Pelajar Pancasila Tema Kewirausahaan - Fatni Mufit; Hayyu Yumna; Aisyah Rehan Fadhillah; Desnita (Universitas Muhammadiyah Metro, 2025)
Strengthening the Pancasila Student Profile (P5) is an essential aspect of implementing the Merdeka Curriculum, aiming to build student character through project-based learning. This study aims to develop and validate a P5-based E-Worksheet (E-LKPD) titled